Randomized Crossover Trial of the Impact of Morning or Evening Dosing of Antihypertensive Agents on 24-Hour Ambulatory Blood Pressure: The HARMONY Trial. Issue 4 (October 2018) - Poulter, Neil R.; Savopoulos, Christos; Anjum, Aisha; Apostolopoulou, Martha; Chapman, Neil; Cross, Mary; Falaschetti, Emanuela; Fotiadis, Spiros; James, Rebecca M.; Kanellos, Ilias; Szigeti, Matyas; Thom, Simon; et al.
Abstract : Some data suggest that nocturnal dosing of antihypertensive agents may reduce cardiovascular outcomes more than daytime dosing. This trial was designed to evaluate whether ambulatory blood pressure monitoring levels differ by timing of drug dosing. Patients aged 18 to 80 years with reasonably controlled hypertension (⩽150/⩽90 mm Hg) on stable therapy of ≥1 antihypertensive agent were recruited from 2 centers in London and Thessaloniki. Patients were randomized to receive usual therapy either in the morning (6 AM–11 AM) or evening (6 PM–11 PM) for 12 weeks when participants crossed over to the alternative timing for a further 12 weeks. Clinic blood pressures and a 24-hour recording were taken at baseline, 12, and 24 weeks and routine blood tests were taken at baseline. The study had 80% power to detect 3 mm Hg difference in mean 24-hour systolic blood pressure (α=0.05) by time of dosing. A 2-level hierarchical regression model adjusted for center, period, and sequence was used. Of 103 recruited patients (mean age, 62; 44% female), 95 patients (92%) completed all three 24-hour recordings. Mean 24-hour systolic and diastolic blood pressures did not differ between daytime and evening dosing. Similarly, morning and evening dosing had no differential impact on mean daytime (7 AM–10 PM) and nighttime (10 PM–7 AM) blood pressure levels nor on clinic levels. Stratification by age (⩽65/≥65 years) or sex did not affect results. In summary, among hypertensive patients with reasonably well-controlled blood pressure, the timing of antihypertensive drug administration (morning or evening) did not affect mean 24-hour or clinic blood pressure levels. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01669928.